STUDI TENTANG KREATIVITAS GURU IPS DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MASA PANDEMIC COVID-19 (Deskriptif Kualitatif, pada kelas 7 di MTS Miftahul Huda Tegalwaru Karawang) - Cici Karmila, - (2020)
This research was motivated by the current conditions and situation, namely the Covid19 pandemic. And also various other background problems such as: students' interest in social studies learning is not satisfactory (still low) compared to the grades when they entered, the learning resources used are limited to the teacher (explanatory notes from the teacher) and the only reading book / LKS / module , the unavailability of complete and adequate tools and types of media, all of which are closely related to business.Being a creative teacher, that is, a teacher must choose and sort out the use of learning models, methods and media. So that a creative teacher will help students achieve their learning outcomes. learning outcomes are a change in behavior that each student has, this change in behavior is one of the gains from student learning outcomes. Learning outcomes are also the process of achieving educational goals for students in participating in the process of teaching and learning activities and learning outcomes are very dependent on learning objectives.In this study, researchers used a qualitative approach and descriptive methods. Data collection was carried out by means of interviews, observations, and documentation studies. The findings of this study are: (1) The form of social studies teacher creativity in improving student learning outcomes during a pandemic, (2) What factors can shape social studies teacher creativity in improving student learning outcomes during a pandemic, (3) The impact of creativity social studies teachers in improving student learning outcomes during a pandemic. Keywords: Social Studies Teacher Creativity, Student Learning Outcomes and the Pandemic Period